2017
DOI: 10.7554/elife.26801
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopamine on reinforcement learning and consolidation in Parkinson’s disease

Abstract: Emerging evidence suggests that dopamine may modulate learning and memory with important implications for understanding the neurobiology of memory and future therapeutic targeting. An influential hypothesis posits that dopamine biases reinforcement learning. More recent data also suggest an influence during both consolidation and retrieval. Eighteen Parkinson’s disease patients learned through feedback ON or OFF medication, with memory tested 24 hr later ON or OFF medication (4 conditions, within-subjects desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(63 citation statements)
references
References 70 publications
2
59
2
Order By: Relevance
“…Another interesting observation was that in all groups, learning rates tend to be higher for positive than negative outcomes. Such a relationship between the learning rates has been observed before in a probabilistic choice task, and was proposed to arise because the animals might have learned that one option gives a higher reward on average, so a single reward omission may just be noise and should not change the behavior (Grogan et al, 2017). In summary, the computational modeling indicated that mutations significantly affected only the parameter influencing the preference for the alternative with a higher expected outcome.…”
Section: Resultsmentioning
confidence: 81%
“…Another interesting observation was that in all groups, learning rates tend to be higher for positive than negative outcomes. Such a relationship between the learning rates has been observed before in a probabilistic choice task, and was proposed to arise because the animals might have learned that one option gives a higher reward on average, so a single reward omission may just be noise and should not change the behavior (Grogan et al, 2017). In summary, the computational modeling indicated that mutations significantly affected only the parameter influencing the preference for the alternative with a higher expected outcome.…”
Section: Resultsmentioning
confidence: 81%
“…There was some evidence for a small effect of dopamine in individual learning blocks, particularly before reversal (p(ON<OFF) < 0.05 in block 2, and p(ON<OFF) < 0.15 in blocks 1-5 and block 9). While Parkinson's patients have been shown to exhibit deficits in multiple forms of feedback-based learning, and levodopa has been shown to alleviate such deficits, these effects are not always present, and some studies have found the reverse effect (Shohamy et al, 2004;Cools et al, 2007;Schonberg et al, 2010;Grogan et al, 2017;Timmer et al, 2017). We observed no effect of medication on reaction times, which decreased over the course of the task, particularly after the first block (Figure 2B).…”
Section: Behavioral Resultsmentioning
confidence: 59%
“…Our model used separate parameters to describe, for a given agent, how strongly current value estimates are updated by positive (again) and negative (aloss) feedback (i.e. positive and negative learning rates [20][21][22]29 ), as well as a parameter that determines the extent to which differences in value between stimuli are exploited (b). To understand how medication affects learning in PD we examined the posterior distributions of group-level parameters representing the within-subject medication shift in again, aloss and b (Fig.…”
Section: Medication Reduces Learning Rate For Negative Outcomesmentioning
confidence: 99%
“…In the Q-learning model, the learning rate weighs the extent to which value beliefs are updated based on trial-by-trial RPE. The processing of choice outcomes is known to influence BOLD signals in the striatum, where the sensitivity to RPE is changed when dopamine levels are manipulated 27,28,29 .…”
Section: Medication In Pd Reduces the Sensitivity Of Dorsal Striatum mentioning
confidence: 99%
See 1 more Smart Citation